Temporal-spatial scheduling of electric vehicles in AC/DC distribution networks. (15th September 2022) - Luo, Lizi; He, Pinquan; Gu, Wei; Sheng, Wanxing; Liu, Keyan; Bai, Muke
Abstract: With the rapid development of power electronic technology, the AC/DC hybrid distribution network has become a new trend of distribution system architectures in recent years. And meanwhile, electric vehicles (EVs) equipped with both AC and DC charging interfaces tend to be utilized as ideally dispatchable resources in not only temporal but also spatial dimensions, whose charging/discharging schemes remarkably impact the secure and economical operation of distribution networks. In view of this background, this paper proposes a temporal-spatial scheduling model of EVs in AC/DC distribution networks, targeting at the optimum of the whole network losses as well as the inconveniences of EV users originated from following scheduling instructions. Besides the traditional constraints relevant to EVs' temporal scheduling in just-AC distribution networks, the AC/DC hybrid topology and the restrictions for EVs' spatial scheduling are properly involved in the proposed model. After a reasonable simplification procedure, the proposed model is represented as a Mixed Integer Quadratic Program (MIQP) problem that can be efficiently solved by off-the-shelf optimization algorithms. Through the analyses of a coupled electrical-geographical AC/DC distribution network, the proposed model can bring 6.3% and 6.8% cost savings respectively on two typical days. Highlights: A joint scheduling model is proposed for EVs in temporal and spatial dimensions. An accurate VSC model is adopted in the modeling of AC/DC distribution networks. The charging piles with various typical powers are involved in the proposed study. The model is tested in two typical scenarios with 6.3% and 6.8% cost savings.